'Noticing' as a scaffolding to enhance the vocabulary of esl learners at the faculty of management studies and commerce, university of jaffna - Ramanan, K.L. (university of Jaffna, 2014)
Teaching vocabulary requires the knowledge of what should be taught about words. Richards (1976) and Nation (2001), as cited by McCarten (2007), list them as ranging from the meaning(s) of the word to its connotations. Having these in the back ground, this study intends to utilize an experimental research oriented Task based Language Teaching (TBLT) method whereby the researcher tries to motivate the ESL learners, at the Faculty of Management Studies and Commerce, University of Jaffna, to improve their vocabulary by engaging themselves in capturing photographs of billboards for collecting the English words on them. The primary objective is to make the students see, notice, learn and familiarize the words via taking photographs. The secondary objective is to make their passive vocabulary to be active. Nation (2001) introduced 'noticing' as a prerequisite for learning words. According to him noticing is seeing a word as something to be learned. The research makes the students notice the words and learn by engaging in relevant and interesting activities which are based on TBLT. The research is designed so as to require the target students to take photographs of bill boards of particular shops and to list the English words on them; a pre-test will be conducted to test their background knowledge, tasks will be designed by the researcher and they will be completed and a post-test would be employed to evaluate the improvements in the understanding of those words.
Keywords: Noticing; ESL Learning; Task based language teaching (TBLT); Intentional Learning